Whole Person Care A New Paradigm for the 21st Century - Hutchinson, Tom A.; Hutchinson, Tom A. (Springer New York : Imprint: Springer, 2011)
A ground-breaking new volume and the first of its kind to concisely outline and explicate the emerging field of whole person care process, Whole Person Care: A New Paradigm for the 21st Century organizes the disparate strains of literature on the topic. It does so by clarifying the concept of 'whole person' and also by outlining the challenges and opportunities that death anxiety poses to the practice of whole person care. Whole person care seeks to study, understand and promote the role of health care in relieving suffering and promoting healing in acute and chronic illness as a complement to the disease focus of biomedicine. The focus is on the whole person -- physical, emotional, social, and spiritual. Using concise, easy-to-read language, the early chapters offer practitioners a thorough understanding of the concepts, skills and tools necessary for the practice of whole person care from a clinician-patient interaction standpoint, while the last two chapters review the myriad implications of whole person care for medical practice. An invaluable resource for all areas of medical practice and for practitioners at all stages of development, from medical students to physicians and allied health providers with many years of experience, Whole Person Care: A New Paradigm for the 21st Century will have a profound impact on western medical practice in North America and elsewhere.